Content Cytotoxicity Studies of Colorectal Carcinoma Cells Using Printed Impedance Sensors - Anis Nurashikin Nordin; Irmanisha Ibrahim; Ahmad Fairuzabadi Mohd Mansor; Yumi Zuhanis Has-Yun Hashim; Ioana Voiculescu (Bulletin of Electrical Engineering and Informatics, 2017)
Monitoring the effectiveness of drugs on cancer cells is crucial for chemotherapeutics studies. In-vitro cell-based biosensors can be used as an alternative for characteristic studies of cells’ response to drugs. Cell-based sensors provide real-time measurements and require smaller sample volumes compared to conventional T-flask measurement methods. This paper presents a biosensor that detects in real-time, impedance variations of human colon cancer, HCT-116 cells when treated with anti-cancer agent, 5-Fluorouracil (5-FU). Two different extracellular matrix (ECM); polyaniline and gelatin were tested and evaluated in terms of attachment quality. Polyaniline was found to provide the best attachment for HCT-116 cells and was used for cytotoxicity studies. Cytokinetic behavior indicated that 5-FU inhibited HCT-116 cells at IC50 of 6.8 µg/mL. Trypan blue exclusion method for testing cell viability was used to validate the impedance measurements, where the cancer cell concentrations were reduced to ~35% when treated with 2.5 µg/mL, and 50% when treated with 6.8 µg/mL. The results generated by the microfabricated impedance biosensor are comparable to the Trypan blue method since both gave similar cell growth trend. It can be concluded that the impedance biosensor has potential to be used as an alternative method in drug testing applications.